IMPLEMENTASI CHATBOT BERBASIS ARTIFICIAL NEURAL NETWORK UNTUK MENDUKUNG EFISIENSI LAYANAN KONSULTASI DI PT LOKAKITA KREATIF INDONESIA - Harist, Muhammad Abdul; Sopingi, Sopingi; Irawan, Ridwan Dwi (Infotech: Journal of Technology Information, 2025)
The rapid development of information technology has driven companies to innovate in delivering faster and more efficient services. PT Lokakita Kreatif Indonesia, a company engaged in consulting and mapping services, often receives recurring questions from clients, which were previously handled manually. To address this issue, this study aims to design and develop a Chatbot system based on Artificial Neural Networks (ANN) that can understand user intent and provide automated responses. The system was developed through several stages, including data collection, text preprocessing, ANN model training using Keras, and integration into a web application built with Flask. The dataset was compiled from frequently asked questions submitted by clients and processed into a machine-readable format. Testing results show that the Chatbot can provide accurate answers with an accuracy rate of up to 87% and a relatively fast response time. These findings indicate that the system can assist the company in delivering initial consultation services in a consistent and autonomous manner. The Chatbot not only improves work efficiency but also opens opportunities for further development through integration with other communication platforms.